PERAN MASYARAKAT TERHADAP PELESTARIAN LINGKUNGAN MELALUI KEGIATAN PROKLIM DI DUSUN MENDIRO - Dhian Satria Yudha Kartika; Asaf Khatami Fatwa; Pieter Adam Telaumbanua; Cahya Lingga Wulandari; Sabrina Berliana Putri; Linda Wahyuningtiyas; Abdul Wahid (Jurnal Pengabdian Sosial Indonesia, 2023)
Proklim activities are one of the activities that aim to increase public awareness of the environment, because their role is to create awareness and community cooperation in creating a healthy and clean environment. The aim of Proklim's activities is to create a community that is self-sufficient in terms of climate change resilience with community empowerment-based resilience through good disaster adaptation and mitigation, as well as reducing emissions and Greenhouse Gases (GHG). Mendiro Hamlet is one of the locations where Proklim activities are carried out, because its conditions and potential meet aspects of adaptation and mitigation efforts in climate change. There is conservation land and environmental care activities carried out by the Menduro Hamlet community, creating multi-stakeholder collaboration. So this research is based on descriptive qualitative with primary and secondary data obtained to give results that are in accordance with the reality in the field. Thus the Proklim activities in Mendiro Hamlet were carried out smoothly and produced a clean and healthy environment. Keywords: Proklim, Care for the Environment, Society, prevention effortsDoi: https://dx.doi.org/10.23960/JPSI/v3i1.8-16